Optimisation of the enterprise’s revenue in the conditions of reducing the volume of product output - Bahaliubskaya-Siniakova, Katsiaryna S.; Kalitine, Boris S. (Journal of the Belarusian State University. Economics, 2023)
The work is devoted to the issue of optimisation of an entrepreneur’s revenue in the context of a decrease in the volume of output of a specific product, what is characteristically for the restrictive way of firm’s production development. The studies are based on the economic and mathematical model of an enterprise’s revenue, which includes such parameters as the coefficient of price elasticity of demand, the coefficient of sales decline, the coefficient of revenue decline and the rate of price growth due to inflation. The main regularities of the increase in revenue when the entrepreneur decides to reduce the volume of output are determined, the optimal value of the reduction in the volume of output and the corresponding value of the maximum possible revenue in conditions of a restrictive way of production development are revealed. In addition, as a result of the analysis of the revenue model, it was found that the implementation of the restrictive way of production development by the enterprise is most profitable in relation to goods with inelastic demand with respect to price.
Keywords: revenue; curtailment of production; restrictive way of development; price elasticity of demand